Free-radical gases on two-dimensional transition-metal disulfides (XS2, X = Mo/W): robust half-metallicity for efficient nitrogen oxide sensors - Zhang, Chunmei; Jiao, Yalong; Ma, Fengxian; Kasi Matta, Sri; Bottle, Steven; Du, Aijun (Beilstein Journal of Nanotechnology, 2018)
The detection of single gas molecules is a highly challenging work because it requires sensors with an ultra-high level of sensitivity. By using density functional theory, here we demonstrate that the adsorption of a paramagnetic unpaired free radical gas (NO) on a monolayer of XS2 (X = Mo, W) can trigger the transition from semiconductor to half metal. More precisely, the single-layer XS2 (X = Mo, W) with NO adsorbed on it would behave like a metal in one spin channel while acting as a semiconductor in the other spin orientation. The half-metallicity is robust and independent of the NO concentration. In contrast, no half-metallic feature can be observed after the adsorption of other free radical gases such as NO2. The unique change in electronic properties after the adsorption of NO on transition-metal sulfides highlights an effective strategy to distinguish NO from other gas species by experimentally measuring spin-resolved transmission. Our results also suggest XS2 (X = Mo, W) nanosheets can act as promising nanoscale NO sensors.
Keywords: free radical; half-metallicity; nitric oxide (NO); sensors; spin-polarized

(untitled) - Ko, G.; Kim, H.-Y.; Ahn, J.; Park, Y.-M.; Lee, K.-Y.; Kim, J. (Curr. Appl. Phys., 2010)

(untitled) - Ho, K.-C.; Tsou, Y.-H. (Sens. Actuators, B, 2001)

(untitled) - Zhang, W.; Uchida, H.; Katsube, T.; Nakatsubo, T.; Nishioka, Y. (Sens. Actuators, 1998)

(untitled) - Yamada, T.; Zhou, H.-S.; Uchida, H.; Tomita, M.; Ueno, Y.; Ichino, T.; Honma, I.; Asai, K.; Katsube, T. (Adv. Mater., 2002)

(untitled) - Yang, Y.; Tian, C.; Wang, J.; Sun, L.; Shi, K.; Zhou, W.; Fu, H. (Nanoscale, 2014)

(untitled) - Yu, F.; Wang, T.; Wen, Z.; Wang, H. (J. Power Sources, 2017)

(untitled) - Tang, Q.; Zhou, Z.; Chen, Z. (J. Phys. Chem. C, 2012)

(untitled) - Leenaerts, O.; Partoens, B.; Peeters, F. M. (Phys. Rev. B, 2008)

(untitled) - Kou, L.; Frauenheim, T.; Chen, C. (J. Phys. Chem. Lett., 2014)

(untitled) - Dong, H.; Wang, L.; Zhou, L.; Hou, T.; Li, Y. (Carbon, 2017)

(untitled) - Zhao, S.; Xue, J.; Kang, W. (Chem. Phys. Lett., 2014)

(untitled) - Liu, H.; Li, X.; Chen, L.; Wang, X.; Pan, H.; Zhang, X.; Zhao, M. (J. Phys. Chem. C, 2016)

(untitled) - Wu, G.; Yang, M.; Guo, X.; Wang, J. (J. Comput. Chem., 2012)

(untitled) - Zhang, C.; Jiao, Y.; Ma, F.; Bottle, S.; Zhao, M.; Chen, Z.; Du, A. (Phys. Chem. Chem. Phys., 2017)

(untitled) - Zhang, C.; Jiao, Y.; He, T.; Ma, F.; Kou, L.; Liao, T.; Bottle, S.; Du, A. (Phys. Chem. Chem. Phys., 2017)

(untitled) - Rigoni, F.; Maiti, R.; Baratto, C.; Donarelli, M.; MacLeod, J.; Gupta, B.; Lyu, M.; Ponzoni, A.; Sberveglieri, G.; Motta, N.; Faglia, G. (Nanotechnology, 2017)

(untitled) - Li, H.; Yin, Z.; He, Q.; Li, H.; Huang, X.; Lu, G.; Fam, D. W. H.; Tok, A. I. Y.; Zhang, Q.; Zhang, H. (Small, 2012)

(untitled) - Huo, N.; Yang, S.; Wei, Z.; Li, S.-S.; Xia, J.-B.; Li, J. (Sci. Rep., 2014)

(untitled) - Zhang, W.; Huang, J.-K.; Chen, C.-H.; Chang, Y.-H.; Cheng, Y.-J.; Li, L.-J. (Adv. Mater., 2013)

(untitled) - Perkins, F. K.; Friedman, A. L.; Cobas, E.; Campbell, P. M.; Jernigan, G. G.; Jonker, B. T. (Nano Lett., 2013)

(untitled) - Bryden, J. H. (Acta Crystallogr., 1962)

(untitled) - He, Q.; Zeng, Z.; Yin, Z.; Li, H.; Wu, S.; Huang, X.; Zhang, H. (Small, 2012)

(untitled) - Yue, Q.; Shao, Z.; Chang, S.; Li, J. (Nanoscale Res. Lett., 2013)

(untitled) - Ding, K.; Lin, Y.; Huang, M. (Vacuum, 2016)

(untitled) - O’Brien, M.; Lee, K.; Morrish, R.; Berner, N. C.; McEvoy, N.; Wolden, C. A.; Duesberg, G. S. (Chem. Phys. Lett., 2014)

(untitled) - Bui, V. Q.; Pham, T.-T.; Le, D. A.; Thi, C. M.; Le, H. M. (J. Phys.: Condens. Matter, 2015)

(untitled) - Sik Hwang, W.; Remskar, M.; Yan, R.; Protasenko, V.; Tahy, K.; Doo Chae, S.; Zhao, P.; Konar, A.; Xing, H.; Seabaugh, A.; Jena, D. (Appl. Phys. Lett., 2012)

(untitled) - Zhou, C.; Yang, W.; Zhu, H. (J. Chem. Phys., 2015)

(untitled) - Kou, L.; Du, A.; Chen, C.; Frauenheim, T. (Nanoscale, 2014)

(untitled) - Son, Y.-W.; Cohen, M. L.; Louie, S. G. (Nature, 2006)

(untitled) - Qian, M. C.; Fong, C. Y.; Liu, K.; Pickett, W. E.; Pask, J. E.; Yang, L. H. (Phys. Rev. Lett., 2006)

(untitled) - Kan, E.-J.; Wu, X.; Li, Z.; Zeng, X. C.; Yang, J.; Hou, J. G. (J. Chem. Phys., 2008)

(untitled) - Jiao, Y.; Ma, F.; Zhang, C.; Bell, J.; Sanvito, S.; Du, A. (Phys. Rev. Lett., 2017)

(untitled) - Kresse, G.; Hafner, J. (Phys. Rev. B, 1993)

(untitled) - Kresse, G.; Furthmüller, J. (Phys. Rev. B, 1996)

(untitled) - Blöchl, P. E. (Phys. Rev. B, 1994)

(untitled) - Grimme, S. (J. Comput. Chem., 2006)

(untitled) - He, K.; Poole, C.; Mak, K. F.; Shan, J. (Nano Lett., 2013)